Imaging comparison between 18F-FDG-PET/CT and 18F-flouroethyl choline PET/CT in rare case of thymus carcinoma exhibiting a positive choline uptake - Takesh, Mustafa; Adams, Stefan (Case reports in oncological medicine, 2013)
It is of great value by using PET imaging in oncology to recognize any atypical uptake not related to the underlying disease. That helps in avoiding the false positive finding and may contribute in extending the application range of used radiopharmaceuticals in further disorders. It is well known that radiolabeled choline is an essential PET tracer used currently in prostate cancer. The physiological choline distribution was described. Nevertheless there is still a lack of studies, which describe this distribution in young patients; given that the radiolabeled choline is generally being used in the field of prostate cancer. Whether the thymus exhibits normally a positive choline uptake or not is still unknown. In particular, it is known that the lymphocytes express high affinity of choline transporter and enzymes involving its metabolism. Some cases of thymus carcinoma exhibiting a positive choline had been reported in the literature, however, mostly using 11C-choline. We report a rare case of metastatic thymic carcinoma detected incidentally using 18F-choline-PET in a 78-year-old male patient referred with elevation of prostate specific antigen. Moreover we present a comparison pattern with 18F-FDG-PET modality, in which 18F-choline-PET was turned out to be superior in tumor delineation.